Advances in computing : 13th Colombian Conference, CCC 2018, Cartagena, Colombia, September 26-28, 2018, Proceedings /: 13th Colombian Conference, CCC 2018, Cartagena, Colombia, September 26-28, 2018, Proceedings. (2018) - Unknown
No abstract available